Analysis of Stunting Determinants Incidence in The Working Area Of Aras Kabu Health Center, Deli Serdang Regency, 2025 - Soli Natalia Tambunan; Herlina; Raisha Octavariny (JURNAL KESMAS DAN GIZI (JKG), 2026)
Background: Stunting is a linear growth disorder caused by chronic malnutrition and recurrent infections, characterized by a height-for-age Z-score (HAZ) < −2 SD according to WHO standards. Stunting remains a global and national public health problem, including in Indonesia and Deli Serdang Regency. This condition has serious impacts on cognitive development, productivity, and increases the risk of chronic diseases in adulthood. Stunting is influenced by multiple factors, including food intake, household food security, parenting practices, environmental sanitation, and utilization of health services. Objective: To analyze the determinants of stunting in the working area of Aras Kabu Public Health Center, Deli Serdang Regency, in 2025. Methods: This study used a quantitative analytic design. It aimed to analyze the determinants of stunting among children under five. The study was conducted in the working area of Aras Kabu Public Health Center, Deli Serdang Regency. Results: Based on univariate and bivariate analyses, the prevalence of stunting in the Aras Kabu Public Health Center area in 2025 was 19.25% and was significantly associated with food intake, household food security, parenting practices, environmental sanitation, and utilization of health services. These findings indicate that the five factors are important determinants of stunting and should be prioritized in prevention efforts. Therefore, strengthening the role of primary health care through nutrition education, optimization of community health posts (posyandu), growth monitoring, and promotion of clean and healthy living behavior (PHBS) is necessary, along with cross-sector collaboration, active parental involvement, and engagement of health workers in early detection and prevention. Conclusion: Based on the study findings, there is an association between dietary intake, food security, parenting practices, environmental sanitation, and utilization of health services with the incidence of stunting in the working area of Aras Kabu Public Health Center in 2025. Multivariate analysis also showed that dietary intake was the most influential factor associated with stunting.